Evolving Dimension of Security: Bioterrorism - Yadav, Pankaj Kumar (Unity Journal, 2022)
Bioterrorism became a burning issue in the USA after the human-induced incidence of Anthrax and the attack on WTO in 2001. At present, the world is trapped in the COVID 19 pandemic having an estimated monetary loss of 76.69 billion USD, engulfed more than 4.5 million people, and 211 million suffering to date. There is increasing concern toward bioterrorism globally which can happen either intentionally or due to poor laboratory practices. In recent decades technological progress in bioscience has simplified the development of bioweapons. Moreover, the advancement of genetic engineering is chronic biologically. Over a hundred pathogens have been identified as possible bioterrorism agents. The research article aims to explore bioterrorism as an evolving dimension of threat to the public and national security in developing countries like Nepal. In present article introduction section deals with background, statement of the problem and rationale of our study. The main body deals with biological agents of bioterriorism and their targets, history, present scenario of bioterrorism. Finally, awareness and control measures, challenge and prospects of biosecurity in Nepal. The ubiquity of biological equipment, technical knowledge and ease of production has stimulated the threat of bioterrorism. Some of the challenging dimensions are agroterrorism and bioterrorism because the attack is very difficult to detect and has a devastating effect in a short period. The social and environmental consequences of these attacks can be catastrophic. The study revealed that it would be better to pay attention and go for precaution before the occurrence of bioterror. Improving forensic techniques of the national security wing for detecting and disabling biological weapons will assist in rapid detection. The restriction against easy access to potential bioagents, physical protection, border controls, risk policies and strict law enforcement are the major steps for ensuring biosecurity.